2006
DOI: 10.3354/dao068101
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of macrophage aggregates in brook trout Salvelinus fontinalis and rainbow trout Oncorhynchus mykiss

Abstract: Macrophage aggregates (MAs) occur in various organs of fishes, especially the kidney, liver and spleen, and contain melanin, ceroid/lipofuscin and hemosiderin pigments. They have been used as indicators of a number of natural and anthropogenic stressors. Macrophage aggregates occur in salmonids but are poorly organized, irregularly shaped, and are generally smaller than those in derived teleosts. These features complicate quantification, and thus these fishes have seldom been used in studies correlating MAs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 41 publications
4
40
1
6
Order By: Relevance
“…The melanin was almost absent. Such a distribution of the pigment in brook barbel spleen was in accordance with the data of the other authors [9][10][11]. Moreover, the hemosiderin deposition in MACs indicated to the presence of toxic materials in environment [16].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The melanin was almost absent. Such a distribution of the pigment in brook barbel spleen was in accordance with the data of the other authors [9][10][11]. Moreover, the hemosiderin deposition in MACs indicated to the presence of toxic materials in environment [16].…”
Section: Resultssupporting
confidence: 79%
“…Number, size and pigment composition of MACs depend on various internal, i.e., endogenous factors [10][11][12][13]. Pigmented MACs also depend on the exogenous factors, namely on the presence of toxic materials in the environment [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In Salmoniformes and Clupeiformes, MACs are more difficult to be defined and consequently to be quantified, due to morphological differences with other teleosts. Considering the difficulties in defining and counting MACs, their usefulness in assessment of fish and environmental health is not confirmed yet in salmonids [19]. Moreover, utility of MACs changes in salmonids, as in all teleosts, as biomarkers must be based and supported on previously determined data of normal fluctuations of MACs metrics [17].…”
Section: Introductionmentioning
confidence: 99%
“…All this makes it difficult to compare data and patterns between different fish species. Also, it is evident that there is yet very scarce quantitative data on amounts of PMQ in view of gender and/or year season, though qualitative analyses indicated that those factors may make a difference (Agius and Roberts 2003;Schwindt et al, 2006;Balamarugan et al, 2012). To our knowledge, there are only tree studies that, using salmonid fish and stereological techniques that provided quantitative data, supported the idea that both gender and season/reproductive status influence the amount of PMQ (Rocha, Monteiro and Pereira 1997;Jordanova, Miteva and Rocha 2008;Jordanova et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Their number, size, shape and pigment composition vary depending on factors such as: species (Roberts 1975;Agius 1980Agius , 1985Agius and Roberts 2003;Iwanowitcz et al, 2012); organ (Agius 1979;Kranz and Peters 1984 (Schwindt et al, 2006); age (Agius 1979;Agius and Roberts, 1981;Brown and George 1985;Blazer et al, 1987;Kranz and Gercken 1987;Russo, Yanong and Terrell 2007;Iwanowitcz et al, 2012); reproductive cycle (Jordanova, Miteva and Rocha 2008;Jordanova et al, 2011); nutritional status and health condition (Agius 1981;Agius and Roberts 1981;Agius 1985;Agius and Agbede 1984;Kranz 1989;Mizuno et al, 2002;Gregory et al, 2014;Omnes et al, 2015). Environmental deterioration, and mainly of water quality, can also influence PMQ in various ways (Agius 1985;Peters and Schwarzen 1985;Blazer et al, 1987;Кranz and Gercken 1987;Pulsford, Ryan and Nott 1992;Long et al, 1995;Couillard and Hodson 1996;Meinelt et al, 1997;Fournie et al, 2001;Facey et al, 2005, Iwanowitcz et al, 2012Balamarugun et al, 2012;Beso et al, 2016).…”
Section: Introductionmentioning
confidence: 99%